Epicardial fat thickness in patients with psoriasis vulgaris - Ahmet Bacaksız; Abdurrahman Tasal; Emrah Sevgili; Ercan Erdoğan; Nahide Onsun; Osman Sönmez; Buğçe Topukcu; Emin Asoğlu; Ömer Göktekin (KARE Publishing, 2014)
Objectives: Psoriasis vulgaris is one of the most common skin disorders. Patients with psoriasis carry an excessive risk of coronary artery disease. Visceral adipose tissue around the heart affects the heart and coronaries by secreting proatherogenic mediators. It can be evaluated easily by measurement of epicardial fat thickness (EFT). The aim of this study was to investigate EFT in patients with psoriasis vulgaris. Study design: One hundred and fifteen adult patients (62 male; mean age 33.6+-6.0 years) with psoriasis vulgaris (Group 1) and 60 age- and sex-matched healthy individuals (28 male; mean age, 32.5+-8.3 years) (Group 2) were included in this study. EFT was obtained by transthoracic echocardiography. Disease-specific characteristics of the patients were recorded. Serum glucose, lipid profile and high-sensitive C-reactive protein (hs-CRP) levels were measured. Results: EFT and hs-CRP were significantly higher in Group 1 than in Group 2 (5.7+-1.2 vs. 4.1+-1.0 mm, p<0.001 and 0.52+-0.45 mg/dl vs. 0.19+-0.17 mg/dl, p<0.001, respectively). The psoriasis disease activity score and hs-CRP were found to be independent predictors of EFT in patients with psoriasis vulgaris (β=0.21, t=2.67, p=0.01 and β=0.62, t=7.72, p=0.001, respectively). Conclusion: Our findings indicate that EFT was significantly higher in patients with psoriasis vulgaris compared with the controls. It was more prominent in patients with severe disease.